(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Multidrug resistance among bacterial pathogens is an issue of global concern, especially in commercial food premises. This study aimed to isolate and identify the multidrug-resistant S. aureus from cutting boards of some selected restaurants in Sri Serdang, Selangor, Malaysia. Samples were obtained from the surfaces of 55 plastic cutting boards of 45 restaurants by swabbing and analyzed using 3Mâ„¢ Petri filmâ„¢ Staph Express Count Plate and Disk and further identified using Gram staining, coagulase and catalase tests and growth on mannitol salt agar and Baird Parker agar. Agar-disk diffusion technique was employed for antibiotic resistance against 11 antibiotics, and the results were analyzed based on CLSI. Out of 55 samples obtained, 43.6% (n=24) were found to be positive for S. aureus. Of the 24 S. aureus, 45.8% (n=11) were multidrug-resistant. Resistance to the members of penicillins was 100%, to nalidixic acid (79.2%), to ciprofloxacin (66.7%), to cephalothin (33.3%) and ceftazidime (20.8%). There was no resistance to gentamicin, streptomycin, ceftriaxone, cefotaxime, and sulphafurazole. The emergence of multidrug-resistant S. aureus on the cutting boards is an indication of poor personal and sanitary hygiene and could pose a danger of outbreak due to staphylococcal food poisoning among consumers.